Impact of Brand Coolness in purchase intention in fast food and festival markets - Ferreira, João Filipe Botica (2020)
Companies nowadays face the challenge of selling their products in highly competitive markets where customers possess access to wide sources of information across multiple purchase options. To differentiate themselves they resort (along with other strategies) to developing resonating consumer brand relationships to influence the decision process and generate sales. This thesis investigates the impact of Brand Coolness in Purchase Intention across two markets (Fast Food and Festival markets) in order to take conclusions related to the degree of impact between the constructs and its implication between products with high level involvement in purchase and low level involvement in purchase. By conducting two questionnaires to a combined sample of 306 respondents, this thesis concludes that Brand Personality, Self-Brand Connections and Communal Brand Connections positively impact Brand Coolness. With this positive correlation proved significant, it was also proved that Brand Equity is benefited which translates into a higher Purchase Intention. The data analysis also confirmed a difference in impact across the two markets, where Brand Coolness possessed a higher influence on Purchase Intention in the chosen lower involvement market products. The conclusions withdrawn from this thesis complement previous literature by addressing the existing gap in investigation of Brand Coolness in a purchase behaviour related theme. It also gives brand managers an insight to the impact of consumer brand relationship constructs in intent of product purchasing and its impact across two distinguishable markets.